An Improved Method for Order Reduction of High Order Uncertain SISO Dynamic Systems by Affine Arithmetic - Ramana, Boyi Venkata; Narasimhulu, T.; Rao, P. Mallikarjuna (International Journal of Membrane Science and Technology, 2023)
This article presents a refined algorithm using Modified Polynomial Differentiation (MPD) method through Affine Arithmetic (AA) to reduce the high order uncertain systems. This new algorithm is applicable for the reduction of Continuous SISO systems. Measurement errors due to variation in ambient conditions may result the system as an uncertain system unlike other methods in literature. This strategy, unlike previous ones found in the Iteration literature, can produce a reduced order model that is stable from a original high order uncertain system that is also stable. Applications of Affine Arithmetic steer clear of many of the drawbacks of Interval Arithmetic, including unbounded solutions in a number of important applications. Utilizing common numerical examples from interval literature, the proposed approach has been validated